2020
DOI: 10.4081/jphia.2020.1303
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of scabies outbreak in Takusa district of Amhara Region, Northwest Ethiopia

Abstract: Introduction: Nutritional therapy in the treatment of high blood pressure and heart failure is a real challenge in terms of compliance of sodium restriction for success of the treatment. The study aims to assess the level of patient compliance with the sodium restriction by salt consumption, prescribed by care providers and the associated factors. Materials and Methods: Total daily salt intake was estimated in a cross-sectional study of 166 hypertensive and heart failure subjects monitored in the cardiology de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Previous studies on the elderly with hypertension also showed similar results (21,25). A lack of knowledge about salt in the diet is a factor in non-compliance with a saltreduced diet (26). Other studies have also shown that salt reduction knowledge is positively correlated with salt consumption behavior (27).…”
Section: Discussionmentioning
confidence: 58%
“…Previous studies on the elderly with hypertension also showed similar results (21,25). A lack of knowledge about salt in the diet is a factor in non-compliance with a saltreduced diet (26). Other studies have also shown that salt reduction knowledge is positively correlated with salt consumption behavior (27).…”
Section: Discussionmentioning
confidence: 58%